38.5k views
5 votes
-4(v+1)=6v-8+2(4v+7)

2 Answers

3 votes

Answer:

v = -5/9 or -0.55

Explanation:

Step 1: Simplify both sides of the equation.

−4(v + 1) = 6v − 8 + 2(4v+7)

(−4)(v) + (−4)(1) = 6v + −8 + (2)(4v) + (2)(7)(Distribute)

−4v + −4 = 6v + −8 + 8v + 14

−4v − 4 = (6v + 8v) + (−8 + 14)(Combine Like Terms)

−4v − 4 = 14v + 6

−4v − 4 = 14v + 6

Step 2: Subtract 14v from both sides.

−4v − 4 − 14v = 14v + 6 − 14v

−18v − 4 = 6

Step 3: Add 4 to both sides.

−18v − 4 + 4 = 6 + 4

−18v = 10

Step 4: Divide both sides by -18

-18v / 18 = 10/-18

v = -5/9 or -0.55

User RJardines
by
6.0k points
2 votes

Answer:

v = -5/9

Explanation:

-4(v + 1) = 6v - 8 + 2(4v + 7)

-4v -4 = 6v - 8 + 8v + 14

add 4 to both sides:

-4v -4 + 4 = 6v - 8 + 8v + 14 + 4

-4v = 6v + 8v + 10

-4v = 14v + 10

subtract 14v from both sides:

-4v - 14v = 14v + 10 - 14v

-18v = 10

divide both sides by by -18:

-18v/-18 = 10/-18

v = -5/9

User Sameer Azazi
by
6.4k points